2007
DOI: 10.7150/ijms.4.232
|View full text |Cite
|
Sign up to set email alerts
|

Familial Polycythemia Caused by a Novel Mutation in the Beta Globin Gene: Essential Role of P50 in Evaluation of Familial Polycythemia

Abstract: Two polycythemic subjects from a family with multiple polycythemic subjects were evaluated. Estimation of oxygen affinity of Hb from venous blood gas parameters (P50) revealed low P50 suggesting a high affinity Hb variant. Further work up, which included beta globin gene sequencing, revealed a novel mutation changing a codon to the previously reported high affinity Hb -Hb Johnstown (beta109 Val->Leu). Polycythemic subjects with high affinity Hb variant are asymptomatic with normal life expectancy. Their differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…In those patients with a low value for P50 sequencing of the globin gene to establish and resistance to the glucocorticoids in particular has been shown to be related to an unfavorable event free survival. 3,4 Since the glucocorticoids prednisolone and dexamethasone play a crucial role in essentially all therapy protocols, the development of strategies to reverse resistance to these agents is important to improve ALL treatment efficacy. Recently, we have demonstrated that glucocorticoid resistance in pediatric ALL is associated with increased glucose metabolism, and that inhibition of glycolysis sensitizes prednisolone-resistant ALL cells to glucocorticoids.…”
mentioning
confidence: 99%
“…In those patients with a low value for P50 sequencing of the globin gene to establish and resistance to the glucocorticoids in particular has been shown to be related to an unfavorable event free survival. 3,4 Since the glucocorticoids prednisolone and dexamethasone play a crucial role in essentially all therapy protocols, the development of strategies to reverse resistance to these agents is important to improve ALL treatment efficacy. Recently, we have demonstrated that glucocorticoid resistance in pediatric ALL is associated with increased glucose metabolism, and that inhibition of glycolysis sensitizes prednisolone-resistant ALL cells to glucocorticoids.…”
mentioning
confidence: 99%
“…According to these findings, we strongly suspected the presence of a Hb variant with a high oxygen affinity or 2,3-BPGM deficiency (1)(2)(3)(4)(5).…”
Section: Case Reportmentioning
confidence: 85%
“…Meanwhile, algorithms for a definitive diagnosis are being established for congenital erythrocytosis, for which the number of cases is also small (1)(2)(3)(4). Among these algorithms, a P50 measurement using an apparatus to analyse blood gases is a fast and simple test with proven efficacy that reflects a shift in the ODC (1)(2)(3)(4)(5)24). In addition to a family history, a low P50 level in the present patient was observed using the automated blood gas analyser, which strongly suggested the presence of a high oxygen affinity haemoglobinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations